2020
DOI: 10.3389/fbioe.2020.587658
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances of Chitosan-Based Injectable Hydrogels for Bone and Dental Tissue Regeneration

Abstract: Traditional strategies of bone repair include autografts, allografts and surgical reconstructions, but they may bring about potential hazard of donor site morbidity, rejection, risk of disease transmission and repetitive surgery. Bone tissue engineering (BTE) is a multidisciplinary field that offers promising substitutes in biopharmaceutical applications, and chitosan (CS)-based bone reconstructions can be a potential candidate in regenerative tissue fields owing to its low immunogenicity, biodegradability, bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 139 publications
(151 reference statements)
0
75
0
Order By: Relevance
“…Chitosan has been considered a versatile polymer for tissue engineering applications due to its biocompatibility, controllable biodegradability, and the capability of being processed into different architectures (Hu et al 2020; Tang et al 2020). Amino (-NH 2 ) and hydroxyl groups (-OH) are effective centers for complexing with metal ions and are directly involved in the metal-chitosan coordination process (Hu et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan has been considered a versatile polymer for tissue engineering applications due to its biocompatibility, controllable biodegradability, and the capability of being processed into different architectures (Hu et al 2020; Tang et al 2020). Amino (-NH 2 ) and hydroxyl groups (-OH) are effective centers for complexing with metal ions and are directly involved in the metal-chitosan coordination process (Hu et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan has attracted attention for dentin tissue regeneration due to glycosaminoglycan-like polymeric chains, which favor pulp cells interaction, along with proved biocompatibility, biodegradability into nontoxic components, protein affinity, and hemostatic and antimicrobial potential (Hu et al 2020; Tang et al 2020). Previous in vivo studies have already demonstrated that chitosan scaffolds might be useful for in situ tissue engineering of dentin due to adequate absence of cell/tissue toxicity, promoting cell mobilization and interaction, ultimately with odontoblastic differentiation and mineralized tissue deposition in absence of inflammatory reaction on surrounding pulp tissue (Li et al 2014; Machado et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a new type of "bone trabecular metal"porous tantalum (Ta) has attracted great attention, because it has good biocompatibility, ideal modulus of elasticity, corrosion resistance, and high porosity (Han et al, 2019), which promote cell adhesion, growth, and differentiation; form rich extracellular matrix; and enhance the early biological fixation in both research and clinical applications (Balla et al, 2010a,b;Fraser et al, 2019;Tang et al, 2020). Guo et al (2019) used selective laser melting (SLM) technology to manufacture porous Ta scaffolds with a pore size of 400 Âľm.…”
Section: Inert Metalsmentioning
confidence: 99%
“… 115 , 116 Chitosan-based injectable hydrogels can be used as a delivery platform for the local release of drugs such as antibiotics and antiseptics to prevent infection and inflammation associated with periodontitis, to release growth factors such bone morphogenetic protein-7 (BMP-7) and basic fibroblast growth factor (bFGF) to stimulate regeneration of lost tissue or to deliver MSCs for periodontal tissue reconstruction. 117 – 121 …”
Section: Biomaterials As a Platform For Delivery Of Dental Mscsmentioning
confidence: 99%